In defense of marking up. (March 2020) - Thomas, Devon
Abstract : Whether to physically mark entries in a text during the process of book indexing can be a subject of considerable debate amongst indexers. Devon Thomas provides details on how she uses marking up in the indexing process and considers the advantages and disadvantages of this method.